An achievement test in chemistry (based on U.P.-S.E.C. Practical chemistry) - Noval, Edilberta M.
An achievement test in chemistry based on the behavioral objectives of Chapters I-XII of Practical Chemistry for Secondary Schools by the UP Science Education Center was constructed in this study
Thesis (M.A.T.)--University of the Philippines.
Keywords: Chemistry -- Examinations, questions, etc